Assessing future climate trends and their impact on different fractured rock aquifers in Northern Togo. Issue 11 (17th October 2022) - Akara, Mahawa-Essa Mabossani; Reeves, Donald M.; Gnazou, Masamaéya Dadja-Toyou; Boguido, Goumpoukini
Abstract: Water resources in the West African Sudan Savannah are concentrated in fractured crystalline and sedimentary rock aquifers. Due to their low storage, these aquifers are vulnerable to changes in climate. This study assesses future temperature and precipitation trends in the Koumfab watershed of northern Togo. The impact of these future climate trends on surface water and the two types of fractured rock aquifers is also investigated. A fully integrated hydrologic model of the Koumfab watershed in Northern Togo is used to study the impact of climate change on water resources. Bias-corrected temperature and precipitation from four regional climate models (RCMs) and two greenhouse emissions scenarios are used as climate forcings for the integrated model. Climate projections from the four RCMs indicate a rise (1.4 −5.5 °C) in average temperature, from the control (1971–2000) to the future period (2031–2060). Projected precipitation follows two contrasting trends with some RCMs predicting an increase (by up to 14%) in mean annual precipitation, while others predict a decline (by up to −14%). These changes in precipitation and temperature will have a noticeable effect on groundwater levels and stream flow. The hydrologic model indicates a decline in groundwater levels for all future climate projections by 1.4−5.7 m. The decline in groundwater levels is not uniformly distributed in the two types of aquifers. The decline in the fractured sandstone aquifer will be four times greater than that of the fractured granodiorite/migmatite aquifer. Projected stream flow at the watershed outlet shows increasing (59 -332%) and decreasing trends (−39 −100%). HIGHLIGHTS: Future climate projections are likely to reduce the availability of water resources in Northern Togo. Groundwater storage in the weathered horizon of the West African craton can act as a buffer to mitigate the impact of climate change. Average temperatures are projected to increase by 1.4–5.5 °C for the period 2031–2060 relative to the control period (1971–2000). Precipitation trends for the period 2031–2060 show significant fluctuations (±14%). Graphical Abstract